Impedance-based structural health monitoring under low signal-to-noise ratio conditions - de Castro, Bruno A. [UNESP]; Baptista, Fabricio G. [UNESP]; Ciampa, Francesco (My University, 2018)
One of the most promising nondestructive evaluation (NDE) in structural health monitoring (SHM) systems for the inspection of aerospace and civil components is the impedance-based method. This damage detection technique stands out for its simplicity of implementation using small and low-cost piezoelectric transducers, which can operate simultaneously as both sensors and actuators. Typically, there are two impedance-based damage detection approaches: the conventional electro-mechanical impedance (EMI) technique and the transfer frequency response function (FRF) method. Although many studies have reported the effectiveness of both approaches, numerous practical problems such as the effects of structural noise, mainly at low signal-to-noise ratio (SNR), may alter the measured signals, thus preventing damage detection. This work presents an experimental analysis of white noise signal effects for damage detection in isotropic components by using the above mentioned impedance-based approaches. Experimental results revealed that, by using statistical indices such as the correlation coefficient deviation metric (CCDM) and the root mean square deviation (RMSD), the transfer FRF method was more sensitive to assess damage evolution than the EMI technique under ideal condition. However, in the presence of a noisy environment and low SNR ranging from ~ 20 dB to -20 dB, the conventional EMI technique provided higher accuracy in the detection of material defects.